Earnings Losses of Displaced Workers - Louis S. Jacobson; Robert J. LaLonde; Daniel Sullivan (W.E. Upjohn Institute for Employment Research, 1992)
The 1990-1991 recession has intensified concerns about the consequences of workers' job losses. To estimate the magnitude and temporal pattern of displaced workers' earnings losses, we exploit an unusual administrative data set that includes both employees' quarterly earnings histories and information about their firms. We find that when high-tenure workers separate from distressed firms their long-term losses average 25 percent per year. Further, their losses mount even prior to separation, are not limited to workers in a few industrial sectors, and are substantial even for those who find new jobs in similar firms. This evidence suggests that displaced workers' earnings losses result largely from the loss of some unidentified attribute of the employment relationship.
Keywords: J0; J6; 330; earnings; wages; losses; displaced; dislocated; workers; Jacobson; LaLonde; Sullivan